Cooperation Networks and Embeddedness—The Case of the Portuguese Footwear Sector - Rocha, Rúben (2021)
The purpose of this paper is to explore the role of embeddedness and cooperation networks in the business internationalization process. To achieve the abovementioned purpose, a qualitative methodology was carefully chosen, through which semi-structured interviews were conducted with ten entrepreneurs of the footwear sector in Portugal, as well as with a head of the national footwear business association. In order to process the data obtained by conducting the interviews, content analysis and data coding through the NVivo software were performed. The results suggest that internationalization is essential for companies in the Portuguese footwear sector. In addition to internationalization helping companies to increase their turnover, it allows companies to grow in a more sustainable way. On the other hand, research also allows us to deduce that networks play an important role in the development of the organizations in question, as they facilitate access to various resources indispensable to this growth. Concerning embeddedness, this aspect presents itself as a facet to which special attention should be paid, considering the pre-eminence that respondents attribute to all variables that help to structure this dimension. The conclusions of this study have theoretical and practical implications, which provide empirical evidence of how the internationalization process can influence the activity of Portuguese companies in the footwear sector. In addition, the results contribute to the evolution of existing knowledge about how embeddedness and cooperation networks facilitate the internationalization process